Izzivi slavistike v 21. stoletju: 4. mednarodna znanstvena konferenca Slavistični znanstveni premisleki, zbornik povzetkov (University of Maribor Press, 2021)
Challenges of Slavic Studies in the 21st Century: 4th International Scientific Conference Slavic Scientific Reflections, Book of Abstracts. The linguistic contributions include comparative-historical and dialectological research of Slavic languages, comparative research of modern Slavic languages, sociolinguistic, linguocultural and computer research of Slavic languages, research on the standardization and norms of Slavic languages. In the field of Slavic literature and cultures, we will address topics on Slavic literature in a comparative, interliterary and intercultural perspective, Slavic literature in film, theoretical aspects of the study of contemporary Slavic literature, the interrelationships of Slavic literature and cultures, translations of Slavic literature. The conference will also shed some light on the didactic aspect and perspectives of Slavic studies through the prism of the development of contemporary Slavic studies and the teaching of Slavic languages, literature and cultures.